1969
DOI: 10.1029/ja074i024p05633
|View full text |Cite
|
Sign up to set email alerts
|

Observations of the geomagnetic tail at 500 Earth radii by Pioneer 8

Abstract: In January 1968, Pioneer 8 passed through the extended geomagnetic tail region at 470–580 RE. The magnetic field observations suggest detection of the geomagnetic tail; the observations are similar in characteristics to those observed by Pioneer 7 at 1000 RE, but they indicate a higher percentage of time was spent in the region of an extended, aberrated tail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1970
1970
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…A substantial fraction of the observations of the Earth's distant magnetotail were gained by the passage of Pioneer 8 through the tail region at about 500 RE in January, 1968 [Intriligator et al, 1969;Mariani and Ness, 1969;Scarf et al, 1970;Siscoe et al, 1970;Bavassano et al, 1971;and Scarf, 19711. Intriligator et al [19691 reported the presence of rapidly fluctuating ion spectra which were often different from typical solar wind spectra and also time periods when there was a complete absence of measurable plasma while Pioneer 8 was in the Earth's magnetospheric wake region.…”
Section: T Introduction ---//mentioning
confidence: 99%
“…A substantial fraction of the observations of the Earth's distant magnetotail were gained by the passage of Pioneer 8 through the tail region at about 500 RE in January, 1968 [Intriligator et al, 1969;Mariani and Ness, 1969;Scarf et al, 1970;Siscoe et al, 1970;Bavassano et al, 1971;and Scarf, 19711. Intriligator et al [19691 reported the presence of rapidly fluctuating ion spectra which were often different from typical solar wind spectra and also time periods when there was a complete absence of measurable plasma while Pioneer 8 was in the Earth's magnetospheric wake region.…”
Section: T Introduction ---//mentioning
confidence: 99%
“…Instruments on Pioneer 7 and 8 spacecraft detected what appears to be an extension of the magnetospheric tail (or perhaps a wake) at distances of 1000 and 5QQ earth radii, respectively. Its effects were observed is plasma, magnetic fields, and (on Pioneer 8) ac electric fields [Fairfield, 1968;Intriligator et al, 1969;Mariani and Ness, 1969;Ness et al, 1967a;Scarf et al, 197Q r Siscoe et al, 1970;Wolfe and McKibbin, 19686;Wolfe etal, 1967].…”
Section: Magnetosheath Bow Shock and Distant Magnetospheric Tailmentioning
confidence: 99%
“…Pioneer 7 data, at a distance of 1000 RE downstream, from the earth, reported observations of geomagnetic tail related effects (Ness et al, 1967a;Fairfield, 1968). Pioneer 8, at 5 0 0 RE as it crossed the tail region, also reported tail related phenomenon (Mariani and Ness, 1969). …”
Section: Pioneer Seriesmentioning
confidence: 99%